Wiley Encyclopedia of Biomedical Engineering 2006
DOI: 10.1002/9780471740360.ebs1107
|View full text |Cite
|
Sign up to set email alerts
|

Space Physiology

Abstract: Space exploration has been a dream of humankind ever since Baron von Münchausen, Jules Verne, Tsiolkovsky, Goddard, and many others. However, this intriguing environment is not without risks. The human body has developed over the past thousands of years in the constant presence of gravity. When this gravitational force is no longer acting on the body, changes occur. Some of these changes occur immediately; others progress only slowly. In the past 40 years of human space flight (first orbital flight b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…This fluid shift is the reason astronauts exhibit "chicken legs" and "puffy face" and causes an increase in central venous pressure, which in turn increases cardiac stroke volume and cardiac output. An increased transmural pressure in microgravity along with this cardiac distension results in plasma volume migrating from intravascular to extravascular compartments (Beckers et al 2006). Plasma volume reduction on the order of 17% has been observed on the first day of spaceflight, thus leading to an increase in hematocrit.…”
Section: Cardiovascular System and Deconditioningmentioning
confidence: 99%
“…This fluid shift is the reason astronauts exhibit "chicken legs" and "puffy face" and causes an increase in central venous pressure, which in turn increases cardiac stroke volume and cardiac output. An increased transmural pressure in microgravity along with this cardiac distension results in plasma volume migrating from intravascular to extravascular compartments (Beckers et al 2006). Plasma volume reduction on the order of 17% has been observed on the first day of spaceflight, thus leading to an increase in hematocrit.…”
Section: Cardiovascular System and Deconditioningmentioning
confidence: 99%
“…Since the start of human spaceflight, more than 50 years ago, it was found that microgravity is associated with many adaptations in the cardiovascular system [ 1 4 ]. Space flight is characterized by an absence of gravitational stress, which results in various imperative cardiovascular modifications, such as body fluid redistribution [ 5 , 6 ], cardiac atrophy [ 7 , 8 ], vascular remodeling [ 9 , 10 ], and dynamic cardiovascular regulation [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%